Electroencephalogram in Children who Experienced First Unprovoked Seizure - Arinda Putri Auna Vanadia; Prastiya Indra Gunawan; Abdurachman Abdurachman; Martono Tri Utomo; Hanik Badriyah Hidayati (Universitas Airlangga, 2022)
Highlight: Epiletiform abnormalities on the EEG provide additional clinical infromation about seizures The majority of patients who have a first unprovoked seizure have an abnormal EEG (Abnormal II). Using EEG as a supporting diagnostic tool in patients experiencing their first unprovoked seizures may provide more information to improve treatment ABSTRACT Introduction: The first unprovoked seizure is defined as a series of seizures that occur within 24 hours and are followed by recovery of consciousness with unknown triggering causes such as head trauma, central nervous system infections, tumors, or hypoglycemia. The first unprovoked seizure is a thing that cannot be underestimated. According to a previous study, less than half of those who experience their first unprovoked seizure will have another. An electroencephalogram (EEG) is one of the supporting examinations for the first unprovoked seizure. Objective: This study aims to determine the EEG as the first unprovoked seizure supporting examination. Methods: This is a retrospective, descriptive, observational study with sampling from the patient's medical record at Dr. Soetomo General Hospital Surabaya from January 2017 to December 2018 based on predetermined inclusion and exclusion criteria. Results: The EEG results in children who experienced their first unprovoked seizure were more abnormal (52.9%) than normal (47.1%), with an abnormal EEG breakdown of abnormal II (17.6%) and abnormal III (35.3%). There were no patients in this study who had EEG abnormal I. All patients with EEG abnormal II (17.6%) had an intermittent slow EEG waveform, while all patients with EEG abnormal III (35.3%) had a sharp waveform. The most common location of EEG wave abnormalities was temporal (55.6%). Conclusion: In the first unprovoked seizure, an EEG examination can assist clinicians as a seizure diagnostic assistant tool. It is hoped that the results of the EEG can provide better management of the first unprovoked seizure.